Adherence to inhaled corticosteroids: An ancillary study of the Childhood Asthma Management Program clinical trial - Krishnan, Jerry A. (2011)
BACKGROUND: Information comparing subjective and objective measurements of adherence to study medications and the effects of adherence on treatment-related differences in asthma clinical trials are limited. OBJECTIVE: We sought to compare subjective and objective measurements of children’s adherence to inhaled corticosteroids or placebo and to determine whether adherence to study medications modified treatment-related differences in outcomes. METHODS: In an ancillary study conducted in 3 of 8 Childhood Asthma Management Program Clinical Centers, adherence was assessed by using self-reported and objective data in 5- to 12-year-old children with mild or moderate asthma who were randomly assigned to 200 μg of inhaled budesonide twice per day (n = 84) or placebo (n = 56) for 4 years. The κ statistic was used to evaluate agreement between self-reported adherence (daily diary cards) and objectively measured adherence (number of doses left in study inhalers). Multivariable analyses were used to determine whether adherence to study treatment modified treatment-related differences in outcomes. RESULTS: Adherence of less than 80% was seen in 75% of 140 children when adherence was measured objectively but only in 6% of children when measured by means of self-report. There was poor agreement between objective and subjective measurements of adherence of at least 80% (κ = 0.00; 95% CI, −0.05 to 0.04); self-reported adherence over the 4-year period generally overestimated objectively measured adherence (93.6% vs 60.8%, P < .0001). There was little evidence to indicate that adherence modified treatment-related differences in outcomes. CONCLUSION: Researchers should use objective rather than self-reported adherence data to identify clinical trial participants with low levels of adherence to study treatment.